The future of Asia-Pacific economies: A view from Europe - Ulrich Hiemenz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
Major disturbances in their global environment such as the world-wide recession in the early 1980s, in increasing protectionism in the EC and the US, large exchange rate fluctuations, high and volatile real interest rates and commodity price shocks have not prevented developing Asian countries from accelerating economic and social progress in the 1980s. Real per capital income grew much faster than in the 1970s both in South and East Asia, and the income gap between the Asia Pacific region and industrialised countries narrowed substantially (Table 1). Projections of e.g. the World Bank [1990] and the Nomura Research Institute [Kwan, 1990] indicate that these favourable trends are likely to be sustainable throughout the 1990s. Estimates of per capita income growth range from 5 to 7 per cent for East and Southeast Asia and around 3 per cent for South Asia. The good prospects for the coming decade are, nonetheless, overshadowed by rising uncertainties and concerns about persistent and severe trade imbalances, the emergence of trading blocs and the future destiny of the former socialist economies.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Direktinvestition; Entwicklungshilfe; Asiatisch-pazifischer Raum; Südasien; EU-Staaten; Osteuropa